ANALYZING THE ROLE OF SEMANTICS IN REDUCING WRITING ERRORS AMONG 6TH SEMESTER ENGLISH EDUCATION STUDENTS AT UNIVERSITY OF MUHAMMADIYAH TANGERANG - Riana Andriani Putri; Salsa Sabilla Alin Safitri; Aidil Syah Putra (Media Inovasi Pendidikan dan Publikasi, 2024)
This study examines how semantics can help sixth-semester English education students at the University of Muhammadiyah Tangerang reduce writing errors. The study examines how semantic elements such word choice, sentence structure, and contextual understanding affect written communication's accuracy and clarity, highlighting the importance of semantics. The study attempts to determine efficient methods for incorporating semantic awareness into writing teaching through a thorough examination of typical writing faults and their semantic foundations. Through the use of qualitative research techniques, such as data collecting and error analysis, the study aims to shed light on the semantic difficulties that students encounter and suggest specific treatments that would improve their writing skills. The findings are intended to inform curriculum design, pedagogical practices, and teacher training programmes, with the ultimate goal of providing students with the linguistic skills they need for academic and professional success.